Seed Storage Studies in Aegle marmelos and Feronia elephantum - Sivakumar, V.; Warrier, Rekha. R.; Anandalakshmi, R.; Parimalam, R.; Vijaya Chandaran, S. N.; Gurudev Singh, B. (Indian Forester, 2006)
Aegle marmelos and Feronia elephantum are indigenous medicinal tree species cultivated in many Asian countries. Seeds of these species were studied to improve the viability. As temperature plays major role in improving the viability, seeds were stored at different temperatures like ambient temperature (25 to 28 ° C), 10 to 12 ° C, 0 to −5 ° C in closed plastic containers. Seeds were tested for germination at monthly intervals. Initial germination of fresh seeds was 72 per cent and 94 per cent for A. marmelos and F. elephantum, respectively. At the end of 12 months, seeds of A. marmelos stored in ambient and 10-12 ° C temperature showed higher germination per cent (50% and 45% ) suggesting that the seeds could be stored for long durations under ambient temperature. Storing of A. marmelos seeds under low temperature (0 to −5 ° C) was found to be deleterious. On the other hand, seeds of F. elephantum stored well at 0 to −5 °C with 71 per cent germination after 12 months suggesting that the seeds could tolerate low temperatures.